MEWUJUDKAN KOINONIA YANG MISIONAL: ANALISIS TEOLOGI PRAKTIS TERHADAP PARTISIPASI GMIT BET’EL DALAM MERESPONS ISU RENDAHNYA KUALITAS PENDIDIKAN DI NUSA TENGGARA TIMUR - Russal Reindy Neonufa (Diegesis : Jurnal Teologi, 2024)
The low quality of education in East Nusa Tenggara significantly impacts people's lives. GMIT Bet'el, part of the Gereja Masehi Injili di Timor (GMIT), has a vital role in improving the quality of education, but its participation still needs to be improved. This study analyzes the role of GMIT Bet'el in education using practical theology based on Richard R. Osmer's framework and the missional koinonia theory of John Zizioulas and J. Andrew Kirk, as well as the missio Dei concept of the World Council of Churches (WCC). Using qualitative methods that include four tasks of practical theology—descriptive-empirical, interpretive, normative, and pragmatic—, it was found that a lack of congregational motivation, imbalanced priorities, and financial constraints hampers GMIT Bet'el's participation. This theological reflection emphasizes the need for GMIT Bet'el to become a missional koinonia, focusing on education as part of God's mission through awareness-raising, strategic planning, and wise resource management.